2015
DOI: 10.3389/fped.2015.00040
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Stenosis Precipitates Hyponatremic Hypertensive Syndrome and Posterior Reversible Leukoencephalopathy

Abstract: BackgroundHyponatremic hypertensive syndrome (HHS) is an uncommon disorder usually encountered in the adult population with unilateral renal artery stenosis and is under-recognized in the pediatric population.Case diagnosis/treatmentA 19-month-old male presented with new-onset status epilepticus associated with neurological sequelae, and hypertension to a high of 248/150 mmHg. Lab work revealed significant hyponatremia, elevated peripheral renin activity, and increase in aldosterone and ADH levels. A diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…To the best of our knowledge, there are 23 previously reported pediatric patients with HHS under the age of 15 years, excluding causes such as tumor or Takayasu disease ( Table 2 ). 2 , 4 , 8 20 Including our patient, the male-to-female ratio was 9:15. The average age of onset was 3 years (range: 14 days–12 years).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…To the best of our knowledge, there are 23 previously reported pediatric patients with HHS under the age of 15 years, excluding causes such as tumor or Takayasu disease ( Table 2 ). 2 , 4 , 8 20 Including our patient, the male-to-female ratio was 9:15. The average age of onset was 3 years (range: 14 days–12 years).…”
Section: Discussionmentioning
confidence: 71%
“…Urinary chloride level more than 15 mEq/L (Table 2). 2,4,[8][9][10][11][12][13][14][15][16][17][18][19][20] Including our patient, the male-tofemale ratio was 9:15. The average age of onset was 3 years The clinical course after admission just before catheter therapy: hypertension appeared at day 9, which lasted after administration of several anti-hypertension drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior portion of the brain is more vulnerable because autoregulation and sympathetic activity are relatively weak in the posterior area 2,8,9) . The range of cerebral perfusion pressure in which the autoregulation of cerebral blood flow functions nor mally differs individually 2) .…”
Section: Case Reportmentioning
confidence: 99%
“…HHS is characterised biochemically by hyponatremia, hypokalemia, hypochloremia, metabolic alkalosis, hyperreninemia, hyperaldosteronemia and elevated urinary sodium and protein. [ 3 ] The central pathophysiology in HHS involves activation of the Renin-Angiotensin-Aldosterone system (RAAS) secondary to the unilateral renal ischemia. The RAS-mediated elevation in blood pressure causes pressure diuresis and natriuresis through the contralateral kidney.…”
mentioning
confidence: 99%
“…Revascularisation is preferred for unilateral RAS, usually by percutaneous transluminal angioplasty and authors have reported the normalisation of blood pressure after either angioplasty or nephrectomy. [ 2 3 4 5 ] Our patient had a nonfunctional right kidney, a source of persistent hypertension, hence, right nephrectomy was done.…”
mentioning
confidence: 99%